Weapons of Mass Destruction: Challenges Towards Nonproliferation in the Middle East (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
This article aims to develop a fundamental understanding of the theoretical background to nonproliferation; by defining concepts, i.e. deterrence, disarmament and arms control; discussing the role of culture in shaping security culture, thus approaches to nonproliferation; and focusing on the Middle East in relation to nonproliferation regimes, through the Middle East Peace Process, challenges, obstacles and the role of United States as an external player. It is relevant to argue that nonproliferation regimes (as a response to the nuclear proliferation during the Cold War and to weapons of mass destruction (WMD) proliferation in post-Cold War era) face political, economic, cultural and strategic challenges. These challenges, in the form of non-compliance and non-participation, are especially acute in the Middle East. They need to be addressed through  regional and global security arrangements.